Religious Identity in the Use of Social Media Within Pontianak Muslim Community - Zaenuddin Hudi Prasojo; Muhammed Sahrin bin Haji Masri; Ahmad Fauzi; Nur Rahmiani (Institut Agama Islam Negeri Madura, 2020)
Social media plays a very important role in shaping the identity and trends in todays world. Not only for the young generation, almost all people in every generation have also been “addicted” to social media for their daily need and in other processes through assimilation and integration and building new networks in their communities through online and offline activities. As a result, the emergence of the social media as a medium of communication and information today has many impacts on changes of social structure including the religious identity of its users. This article explores the tendency for the development of religious identity in social media among the Ponianak Muslim community by focusing on the typology of social media users among Pontianaak Muslims and various trends in the religious identity of its users. The work suggests that social media users in the Pontianak Muslim community have three main typologies, namely NetPublisher, NetWorker, and NetAdvocate. And the religious identity tendency of social media users in Pontianak is constructed through religious narratives dominated by conservativism discourses. They are seen through at least three aspects including the tendency of religious affiliation, various religious issues that are often discussed, and responses to trending religious issues in social media by Pontianak Muslim netizens.